2016
DOI: 10.1021/acsami.5b10579
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Functionalization of Fluorinated Graphene and Subsequent Application as Water-based Lubricant Additive

Abstract: Although the fluorinated graphene (FG) possesses numerous excellent properties, it can not be really applied in aqueous environments due to its high hydrophobicity. Therefore, how to achieve hydrophilic FG is a challenge. Here, a method of solvent-free urea melt synthesis is developed to prepare the hydrophilic urea-modified FG (UFG). Some characterizations via transmission electron microscopy (TEM), atomic force microscopy (AFM), Fourier transfer infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 33 publications
0
79
0
2
Order By: Relevance
“…Studies have shown that uorinated graphene can reduce the adhesion of the friction interface and improve the durability of graphene. 35…”
Section: Doped Graphene/graphene Oxidementioning
confidence: 99%
“…Studies have shown that uorinated graphene can reduce the adhesion of the friction interface and improve the durability of graphene. 35…”
Section: Doped Graphene/graphene Oxidementioning
confidence: 99%
“…A different approach, based on a substitution reaction on fluorographene, was successfully employed for the preparation of alkylamino graphenes by the reaction of alkylamines, and amino graphene formation by the use of sodium amide . Also, the reaction of fluorographene with urea led to the partial introduction of amine functionalities and, as a consequence, to water dispersible fluorographene …”
Section: Synthesis Of Graphene Derivativesmentioning
confidence: 99%
“…[46] Also, the reaction of fluorographene with urea led to the partial introduction of aminef unctionalities and, as ac onsequence, to water dispersible fluorographene. [47] Graphene azide represents av ery interesting derivative of graphene. The traditional methodo fp reparation is the same as, for example, amino substituted analogues, by treatment of graphene oxide with sodium azide.…”
Section: Graphene Derivatives Based On Pnictogen Group Elementsmentioning
confidence: 99%
“…Thus, 2D materials are selected as high-performance and environmentally friendly lubricants [45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60]. …”
Section: Introductionmentioning
confidence: 99%